ENHANCEMENT OF ECOLITERACY FOR LANGUAGE LEARNERS USING SONG LYRICS - Rantung, Kezia C. Y.; Widiasmoro, Yohanes M. S.; Dewi, Novita (LLT Journal: A Journal on Language and Language Teaching, 2023)
This study explores song lyrics to use in language teaching to enhance students’ ecoliteracy while developing their language competency. Today’s language teaching goes beyond language proficiency but capability to address such emerging issues in society as ecological crises. Inclusion of authentic teaching materials like song lyrics may motive learners to be proficient as well as ecoliterate. The method used in this research include data selection, i.e., song lyrics from KePal-SPI, Navicula, and Burgerkill that can be utilized in ELT; data analysis consisting of paraphrasing, speculating, and interpreting of the song lyrics; and evaluating their thematic and linguistic appropriateness for classroom use. The results show that, first, the five song lyrics reveal ecological problems like deforestation and biodiversity loss that the singing artists lament and call for preventive actions. Secondly, song lyrics may offer imaginative use of language that can enable learners to think critically and creatively, hence useful language teaching materials.